(Non)Functionality of the Dublin System - Frumarová, Kateřina (Migration and Central Europe: Challenges and Legal Responses, 2024)
The chapter focuses on a key element of EU asylum and migration policy and legislation, the Dublin system. The Dublin system is the mechanism whereby a single state among the EU Member States, as well as Norway, Iceland, Liechtenstein, and Switzerland, is designated to examine and decide on a foreigner’s application for international protection, wherever the application for international protection is lodged within the territory of these states. The chapter explains its nature and function, as well as the main principles of its application in practice, including its historical development and background. The main focus is on a critical analysis of its current functioning and the identification of its fundamental shortcomings. This describes the process of reform efforts in relation to the Dublin system, which appears to be successfully approaching its goal. The existing Dublin III Regulation should be replaced by the “Asylum and Migration Management Regulation”. The text therefore also includes a comparison of these two key regulations. To balance the current system whereby a few Member States are responsible for most asylum applications, a new solidarity mechanism is being proposed that is simple, predictable, and workable. The new rules combine mandatory solidarity with flexibility for Member States as regards the choice of individual contributions. The chapter also includes statistical data related to the application of the Dublin system in practice in the EU Member States.Keywords: Dublin system, international protection, asylum, migration, refugee, reform